2018
DOI: 10.3389/fphys.2018.00107
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Tissue-Specific Expression Profiles of Odorant Binding Protein and Chemosensory Protein Genes in Bradysia odoriphaga (Diptera: Sciaridae)

Abstract: Bradysia odoriphaga is an agricultural pest insect affecting the production of Chinese chive and other liliaceous vegetables in China, and it is significantly attracted by sex pheromones and the volatiles derived from host plants. Despite verification of this chemosensory behavior, however, it is still unknown how B. odoriphaga recognizes these volatile compounds on the molecular level. Many of odorant binding proteins (OBPs) and chemosensory proteins (CSPs) play crucial roles in olfactory perception. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 68 publications
13
42
0
Order By: Relevance
“…The main host plant of B. odoriphaga is Chinese chive ( Allium tuberosum Rottle ex Spreng), a perennial vegetable that originated in China and is widely cultivated in East Asia . Bradysia odoriphaga larvae usually accumulate in the roots, bulbs and even immature stems of Chinese chives, making the pest hard to control, leading to significant production losses of Chinese chives …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main host plant of B. odoriphaga is Chinese chive ( Allium tuberosum Rottle ex Spreng), a perennial vegetable that originated in China and is widely cultivated in East Asia . Bradysia odoriphaga larvae usually accumulate in the roots, bulbs and even immature stems of Chinese chives, making the pest hard to control, leading to significant production losses of Chinese chives …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Bradysia odoriphaga larvae usually accumulate in the roots, bulbs and even immature stems of Chinese chives, making the pest hard to control, leading to significant production losses of Chinese chives. 22,23 Neonicotinoid insecticides act on the insect nicotinic acetylcholine receptor, and possess high control activity against sucking pests and some dipteran, coleopteran and lepidopteran pest species. [24][25][26] Because B. odoriphaga larvae usually accumulate in the bulbs of Chinese chive plants, neonicotinoid insecticides such as imidacloprid and thiamethoxam have good field control efficacy towards B. odoriphaga due to their internal conduction within the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Chemosensory proteins, including olfaction-related genes in insect antennae, play important roles in olfaction ( Zhang L. W. et al, 2016 ; Wang et al, 2017 ). Previous studies have reported the antenna-specific expression of CSPs in insects ( Zhao et al, 2018 ). To confirm the reliability of the selected RGs, the expression profiles of the target gene CYP3A and CSP8 were determined in different concentrations of BaP and adult tissues, respectively, and independently normalized with the two most stable RGs as well as the least stable RGs.…”
Section: Methodsmentioning
confidence: 99%
“…Studies involving OBP identification (Li L. et al, 2017;Zhao et al, 2018), protein structural analysis (Northey et al, 2016;Falchetto et al, 2019), immunocytochemistry in specific olfactory sensilla Zhang et al, 2018), ligand binding properties (Sun et al, 2017(Sun et al, , 2018, and in vivo RNA interference (Yin et al, 2018;He et al, 2019) have demonstrated that insect OBPs play crucial roles in odorant discrimination, binding, and transportation. These proteins carry lipophilic odorants to the olfactory receptor cells in the sensillar lymph surrounding the sensory dendrite (Pelosi et al, 2014(Pelosi et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%